2015
DOI: 10.1371/journal.pone.0121889
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III Deficiency in Indian Patients with Deep Vein Thrombosis: Identification of First India Based AT Variants Including a Novel Point Mutation (T280A) that Leads to Aggregation

Abstract: Antithrombin III (AT) is the main inhibitor of blood coagulation proteases like thrombin and factor Xa. In this study we report the identification and characterization of several variants of AT for the first time in Indian population. We screened 1950 deep vein thrombosis (DVT) patients for AT activity and antigen levels. DNA sequencing was further carried out in patients with low AT activity and/or antigen levels to identify variations in the AT gene. Two families, one with type I and the other with type II A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, rs2227589 with haplotype in the SERPINC1 gene of FV Leiden carriers showed significantly decreased antithrombin levels (Segers et al, 2014). However, another familial study showed that both rs2227589 carriers and noncarriers have low antithrombin levels (Bhakuni et al, 2015). Thus, variations located in the coding regions of SERPINC1 but not the rs2227589 (C > T) located in the intron may cause antithrombin deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, rs2227589 with haplotype in the SERPINC1 gene of FV Leiden carriers showed significantly decreased antithrombin levels (Segers et al, 2014). However, another familial study showed that both rs2227589 carriers and noncarriers have low antithrombin levels (Bhakuni et al, 2015). Thus, variations located in the coding regions of SERPINC1 but not the rs2227589 (C > T) located in the intron may cause antithrombin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study of normal Spanish Caucasian showed a functional effect of the rs2227589 on antithrombin levels (Anton et al, 2009). The findings regarding the association between rs2227589 and antithrombin levels were inconsistent among different studies (Segers et al, 2014; Bhakuni et al, 2015). Furthermore, the association between rs2227589 and the risk of VTE in Northern European, American, and Norwegian populations is inconsistent (Tregouet et al, 2009; Austin et al, 2011; Dahm et al, 2012; Jiang et al, 2017; Kajuna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The gene contains 15 exons, ranging from 43 bp to 1213 bp in size and 14 introns ranging from 180 bp to 5 kb in size. The human coding sequence contains 2094 base pairs encoding 698 amino acid peptides and methionine synthase (MS) plays an important role in maintaining intracellular levels of methionine, tetrahydrofolate and homocysteine at appropriate levels [26]. If the MTRR gene mutates, the level of homocysteine in plasma may be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Type II AT deficiency can be further divided into additional subtypes: type IIa caused by mutations in the thrombin binding site, type IIb caused by mutations in the heparin binding site or type IIc in which mutations near the reactive center loop have pleiotropic effects on both heparin and thrombin interactions ( 56 ). Interestingly, a SERPINC1 variant causing type II AT deficiency has been shown to induce polymerization of AT in the plasma ( 57 ). This mechanism is distinct from other SERPIN family variants described that destabilize protein structure and cause intracellular aggregation and retention.…”
Section: Antithrombinmentioning
confidence: 99%